Warisan Metode Pendidikan Islam untuk Generasi Millennial - Zaini Miftah (Al Ulya: Jurnal Pendidikan Islam, 2019)
One of the inheritances of Islamic teachings which is very fundamental in achieving educational outcomes is the learning method. Therefore, this learning method will be very effective and active in encouraging students to be able to develop their potential to be better, ranging from intelligence, personality, character and skills that are useful for themselves and society. Islamic religious education and humans have a very fast dynamism, where Islamic religious education will survive for all ages, so that whenever and anyone who learns it will be able to receive the same and complete understanding of the sources of Islamic religious education, while humans when attached as social beings then there will be a challenge for him to be able to accept the changing times. This writing method is a literature review with a descriptive and exploratory approach which can be concluded that the method of Islamic religious education is an educational method with regular and systematic work and thinking of all the factors that exist to achieve the objectives of Islamic religious education, to deliver material Islamic education effectively and efficiently requires dynamic methods and approaches, including the Hiwar Qur'ani and Nabawi Method, the Stories of the Qur'ani and Nabawi, Amtsal Qur'ani and Nabawi, Uswah Hasanah, Tadrib and Tajribah, Ibrah and Mau 'Idzah, and Targhib and Tarhib